Audit sampling: a simulation study - Abdul Hamid, Mohamad Ali (Universiti Putra Malaysia, 1994)
Auditors use extensive auditing techniques to audit financial statements in an effort to accumulate evidence. However. auditor always sought a cheaper audit technique that does not compromise much on the quality of the audit. One of techniques used by auditor using cost-effective and efficient sampling plan. In practice. auditors use small sample size as minimum as 25 items. Therefore. this simulation exercise is to test whether the given sampling plan has a reasonable chance of picking up errors and estimating the degree of value error that actually exists in an accounting population . We conclude that those firms using samples of less than 50 units for auditing accounting populations with low error rates have a low probability of picking up error. Therefore. we suggest that the minimum sample size per population should increase to at least 50 units. in order to improve their error detection process and ultimately the quality of their audit.